ATENSI MASYARAKAT TERHADAP PROGRAM CITARUM HARUM (Studi Kasus Masyarakat Desa Pameuntasan Kabupaten Bandung) - Jafar Al Faudzi, - (2021)
The Citarum Harum program is one that is expected to solve all environmental pollution problems in the Citarum river. The problem that underlies this research is to find out about people's attention to the Citarum Harum program. the purpose of this study is to get an idea of how people's attention is towards the Citarum Harum program. The research method used in this research is the method of case study. Data was obtained through the study of literature and supplemented with data by interviews to sources. The sources in the study are community, environmental activists, and students. The data that has been obtained is subsequently analyzed through three phases of data reduction, data presentation, and conclusion. The contamination of the Citarum river's environment by household garbage or industrial sewage is the main reason the Citarum Harum program was created. People's attention to the Citarum Harum program is likely to change, which, when it is intense, will increase community attention and vice versa. The inconsistency of society is simply participation in following the programs of Citarum Harum. The result of this lengthy presentation process eventually leads to research on a must for at least reference and consideration to help solve the problems associated with the society's response to the Citarum Harum program.